Spatio-temporal Trend Analysis Of Hydro-climatic Variables Of The Northern Region In Sri Lanka - Nagamuthu, Piratheeparajah (2022)
In recent decades, Sri Lanka has experienced severe floods and droughts, causing health issues and agricultural and income losses. This study evaluated the Spatio-temporal trend of historical and future hydro-climatic variables in the northern region of Sri Lanka. Overall, northern Sri Lanka faced an increase in drought severity during the southwest monsoon season but increased flood severity during the northeast. The trend analysis shows that temperature, precipitation, and evaporation from 1970 to 2019 have increased by 0.44 °C /decade, 18.76mm/decade to 37.68 mm/decade, and evaporation increased by 17%, respectively. More than 50% of the total rainfall is recorded within two weeks, especially from the 20th of November to the 05th of December every year. In the 2020-2100 period, precipitation and temperature are projected to increase by 1.13°C (1.81°C) and 106.19 mm (186mm) under the RCP4.5 (8.5) scenario, respectively as compared to the baseline from 1970 to 2019. There is a strong negative correlation between the reduced number of rainy days and the runoff volume, with an R-value of - 0.70; this indicates and confirms that reduction of rainy days increased the runoff in this region due to the high intensity of the rainfall within a short period. The water availability of the reservoirs significantly dropped during the latter part of the first inter monsoon season, leading to the impact on water supply and demand in the study area. Spatially compared to other parts, the temperature of the western region of the study area has been increasing rapidly by 0.04°C and the middle part of the study area is experiencing an increasing pattern of 9mm rainfall more than other areas.